Assessment of Radiation Dose Associated with the Atmospheric Release of 41Ar from the TRIGA Mark-II Research Reactor in Bangladesh - M. Ajijul Hoq; M. A. Malek Soner; S. Khanom; M. J. Uddin; M. Moniruzzaman; M. S. H. Chowdhury; A. Helal; M. Abu Khaer; S. M. T. Hassan; M. Tareque Chowdhury; M. Mizanur Rahman (Science and Technology of Nuclear Installations)
A major concern for nuclear research reactors under normal operating conditions is that they may release radioactive elements into the atmosphere, endangering public health and the environment. The present study concentrated on the detailed radiological dose assessment resulting from the atmospheric release of 41Ar activity from the TRIGA Mark-II research reactor in Bangladesh during its normal operational condition at full power of 3 MW. The total effective dose equivalent (TEDE), ground deposition activity, organ-committed dose, and pathways dose values have been evaluated under different weather conditions using the HotSpot 3.1.2 code. The weather data have been gathered from the Bangladesh Meteorological Department (BMD), Dhaka. Two significant seasons with various weather stability effects have been considered for dose analysis. Atmospheric dispersion of 41Ar was evaluated using the Gaussian plume model. From the obtained results, the maximum TEDE of 4.06 × 10−9 Sv at 0.19 km distance from the reactor site for stability class B during the summer season is found to be well below the annual effective dose limit of 1 mSv recommended by the ICRP. During the rainy season, the maximum TEDE of 1.76 × 10−9 Sv at 0.92 km distance for stability class E is also found to be negligible compared to the dose limit. From the organ-committed dose analysis, skin is investigated as the highest dose absorber compared to other organs. The pathways dose analysis concludes that the submersion and ground shine doses are observed to be maximum at 0.20 km and 1.0 km distances for the summer and rainy seasons, respectively. Based on the identified results, dose values have been found to be within the limiting values, ensuring environmental and human health safety. Such comprehensive dose analysis due to the atmospheric release of 41Ar activity is very significant from the perspective of ensuring the radiological and environmental safety of research-type nuclear reactors under normal operational conditions.